Prevalence of Radix Entomolaris in Patients at a Multidisciplinary Tertiary Care Hospital of Jharkhand, India - Viswanath, Butta; Mohan, Sumit; Priyank, Harsh; Kumar, Gaurav (Journal of pharmacy & bioallied science, 2025)
ABSTRACT Aim: To investigate the incidence of radix entomolaris in mandibular molars in patients reporting to a tertiary care center in Jharkhand. Materials and Methods: 2640 mandibular molars were assessed using intraoral periapical digital radiography where the total incidence of radix entomolaris and the ratio of their occurrence among gender and location were evaluated. Results: The overall incidence of radix entomolaris was found to be 2.5% with its prevalence in 1.14% females and 1.36% male participants. A nonsignificant difference in the incidence of radix entomolaris was also observed between females and males on the right and left sides. Conclusion: This study confirms a 2.5% prevalence of radix endomolaris, thus warranting requirement of a thorough radiological and clinical assessment before initiation of endodontic therapy.